Virus in the computer and smartphone system / Mohammad Faiz Hafizuddin Johari - Johari, Mohammad Faiz Hafizuddin (Faculty of Art and Design, 2015)
The purpose of this research is to do research on how far a computer virus can go. It because computer virus is same to human virus that can transfer from one person to another or from a computer to other computer. For the human virus it will infected on the person organ it same goes to the computer. The computer system will be infected by the virus and some of the file might be corrupt or damage. There are several types of virus like malware, spyware, Trojan, etc. Each virus here gives different kind of problem to the computer and the way they infected the computer. Some ofit uses to stole other person information, or just make the computer crash rapidly and the way the infected the computer is unique. Just lil(e malware, it infected by phishing, or pop-up from a website. How to get more information about this virus is by making an interview to knowledgeable programmer. This because this programmer has learn more deeply on how the virus work, an even how the virus been produce. There will be few programmers that will be interview. Also the information from the books is really useful and the internet could be useful to. Malware is short term for malicious software. This software used to disrupt computer operation, gather sensitive information, or gain access to private computer systems. It can appear in the form of executable code, scripts, active content, and software. 'Malware' is a general term used to refer to a variety of forms of hostile or intrusive software. The term bad-ware is sometimes used and applied to malware and unintentionally hannful software. Malware includes computer virus, worms, Trojan horses, ransom-ware, spyware, adware, scare-ware, and other malicious programs. As of 20 11 the majority of active malware threats were worms or Trojans rather than viruses. In law, malware is s·ometimes known as a computer contaminant, as in the legal codes ofseveral places in this world. Malware is often disguised as, or embedded in non-malicious files. Spyware or other malware is sometimes found embedded in programs supplied officially by companies, e.g. downloadable from websites that appear useful or attractive, but may have malware in it. Example, additional hidden tracking functionality that gathers marlceting statistics. An example of such software which was described as illegitimate is the Sony rootkit. A Trojan embedded in CD sold by Sony, which silently installed and concealed itself on purchases computers with the intention of preventing illicit copying. It also reported on user listening habits and created vulnerabilities that were exploited by unrelated malware. The term malware only applies to software that intentionally causes harm. Software that causes harm due to bugs or poor design is not classified as malware. For example some legitimate software written before the year 2000 had errors that caused serious malfunctions when the year change from 1999 to 2000, these programs are not considered malware. Software such as anti-virus, anti-malware, and firewalls are used by home user and organizations to try safeguard against malware attacks. As of 2012 approximately 60 to 70 percent of all active malware used some kind of click fraud to monetize their activity. The solution of this virus problem is to know on how this virus work and how to defend it especially for computer or smartphone user.